Coherent acoustic control of a single silicon vacancy spin in diamond - Smarak Maity (Nature Portfolio, 2020)
Qubits in solid state systems like point defects in diamond can be influenced by local strain. Here the authors use surface acoustic waves to coherently control silicon vacancies in diamond, which have the potential to reach the strong coupling regime necessary for many applications.